Caracterização do perfil metabólico e epidemiológico de vacas leiteiras mestiças no pós-parto - Komatsu, Raquel Satomi (2017)
The objective of this study was to characterize the serum biochemical profile at birth and postpartum of crossbred dairy cows raised in extensive production systems in the city of Uberlândia, Minas Gerais, according to the calving season and to perform a survey of the main diseases occurred at this stage. A total of 208 cows from 10 farms, accompanied at three times: at calving, at 60 and 120 days in lactation (DEL), participated in the experiment. At each moment the general clinical examination of the animals was carried out, the diagnosis of diseases was carried out and a blood sample was collected from each animal. The occurrence of affections was 15.9%, being 8.2% retained placenta, 4.3% dystocia, 1.9% uterine prolapse, 1.0% claudication and 0.5% clinical mastitis. The highest occurrence of these diseases occurred in the winter (69.7%), which coincided with the higher milk production and body weight. The biochemical profile of these animals was marked by hypocalcemia, hypophosphatemia, hypoalbuminemia and low levels of urea, demonstrating that mineral and protein supplementation was not sufficient to improve the metabolic profile of these animals. The energetic profile showed an increase in NEFA on the day of delivery, signaling that there was BEN and adipose tissue mobilization in this period. The metabolic imbalance presented by the herds reveals that there were nutritional management failures in the winter and summer periods that need to be corrected to reduce the affection of affections and to increase milk production.